Low carbon dispatch of electricity-gas-thermal-storage integrated energy system based on stepped carbon trading - Rui Guo; Hanwen Ye; Yan Zhao (Energy Reports, 2022)
In the construction of the energy Internet and the environment of national environmental protection, China has proposed the establishment of carbon trading markets, such as policy mechanisms, and energy conservation and emission reduction have also become the most popular topic. To this end, the article proposes a low-carbon operation mode of an integrated energy system. First, build a combined electricity-gas-heat-storage structure based on energy conversion and storage devices; then, introduce a stepped carbon trading mechanism and establish a hierarchical calculation model, that is, calculate carbon trading costs based on the carbon emission range; then, Establish a low-carbon scheduling model, in which the goal is to minimize the sum of power generation costs and CO2 emissions transaction costs, and take into account safety constraints. Finally, a case study will be conducted to test the effectiveness of the proposed model.